Assessment of the I-PASS program on nursing shift handover in CCU and ICU wards: The use of a new approach in the nursing profession - ali omidi; Mohammadreza Rajabalipour; shima arab; Tayebeh Mokhtari Sorkhan (Golestan University of Medical Sciences, 2023)
Background: Shift handover is one of the critical tasks and major challenges among health care providers in hospitals. Most serious errors are caused by communication problems related to shift handover. Thus, it is essential to implement effective programs to overcome shift handover challenges in hospitals. This study aimed to evaluate the effects of the I-PASS (illness severity, patient summary, action list, situation awareness and contingency planning, and synthesis by receiver) program on nursing shift handover in hospital wards in southeastern Iran. Methods: This study used a quasi-experimental design with a before-and-after method (without a control group) and was conducted in Pasteur Hospital in Bam City from January to March 2021. Sampling was performed using the census method. Participants included 47 nurses who work in critical care unit (CCU) and intensive care unit (ICU) wards. All nurses received shift-handover training based on the I-PASS program for 4 weeks (45-minute sessions weekly). The standardized I-PASS assessment tool was used in this study. Data were analyzed using SPSS version 25, along with the chi-square test, independent t test, and paired t test. P values less than 0.05 were considered statistically significant. Results: Among the participants, 89.4% were female, and 68.1% worked in the ICU ward. The mean age of the nurses was 33.25 ± 5.00 years old, and the mean year of their work experience was 8.08 ± 5.27 years. There was a significant difference in the mean scores of nursing shift handover before and after the intervention in the CCU ward from 1.88 ± 0.32 to 3.62 ± 0.98 (P = 0.018) and in the ICU ward from 2.37 ± 0.84 to 2.93 ± 0.35 (P = 0.013). Also, the mean scores of the CCU ward were higher than those of the ICU ward after the intervention (P = 0.01). Conclusion: The I-PASS program can overcome many challenges in nursing shift handover and workflow. Therefore, this method can be a suitable alternative to the common methods of shift handover and patient delivery in hospital wards.